MODIF'IKASI MESIN BOBOK KAYU UNTUK PENINGKATAN PRODUKTIVITAS MEBEL INDUSTRI KECIL - -, Slamet Karyono; -, Edy Purnomo (Universitas Negeri Yogyakarta, 2004)
Theproblemsof thefurniture industrytargetareabouttheeffectiveness ofthe useofwood chiselandbit machine becauseithasn't fix machinebench for woodlayingand themachinepositionthat notergonomic.Theseproblemsmake settingtime longer,woodpositionunstable becauseof unfixbench,theviceeasy to brokenbecauseof instabilityof wood,imprecisionof holeposition,and theexhaustedoperatorbecause ofthe machine position.The maingoalof thisvoucherprogramisto modiwood chiseland bitmachineforpreparingtheconnectionbetweenpinand its holeat u.D. TANGGUH,smallscalefurnitureindustry,sothatproductivifl,andqualityof the furniturewill beimproved.Formassproduction,everystep mustbe doneperfectlyandcarefullysothateverypartcanbeconnectedandconstructedcorrectly.Becauseofthereasonabovewood andchiselmachinethatstrong,easyto operate,easytolaywoodaccurately,and ergonomicmustbe developed.Woodandchiselmachinethatbe developedhas 220cmlengthand 30cmwidthof itsbenchso thatthe wood with200crn lengthormorecan be supportedaccuratelyespeciallyat itsparallelpositionto themachinevice.Foroperaiingthemachineeasily,themachinebenchismadeapproximately50cm heightso that theoperatorwithsitdown positioncanoperatethemachinewithoutexhausted.Thewoodchiselandbitmachinecanmakeiheholeapproximately7 cmdepthand 1 crnwidth..Theresultof themachine performancetestshow thatthemachinecan beoperatedeasilywithoutexhausted.Thehole is easilytobe madeonwoodwith200cmlengthwithoutsettingwood position.The holepositionisautornaticallyperpendicularto thehorizontallineof thewoodsothatinaccordancewiththe holepositionon the wood.Thereisnovibrationonbenchandthemachine.Thisconditionshowsthatthe constructiondesignisstrongenoughto thevibrationof themotorrevolutionandtheholefeeding.